(3eGdc Hf fHj (B:s (3GdCYeGd GdcGedI (B/s - (3eGdc, Hf fHjs ((3OeTb (B:s (3OGQ GdacQ ddWHGYI h GdfTQ h GdJhRjY ,s, 2017)
(3dbO GSJMceJ ZQHI eGdc Hf fHj Ydi GdSGMI GdacQjI(B: (3fJjLI efgLjJg GdUGQeI GdJj QJH CacGQg YdjgG; hQDjJg GdHYjOI GdJj JVY eTQhYg GdfgVhj aj EWGQg GdEfSGfj GdTGed, haj ehbYg Ydi eSGQ GdOhQGJ GdMVGQjI, eJejRkG HPdc Yf SGFQ eacQj MQcI GdfgVI; HTbjgG(B: (3GdSdaj hGdMOGKj, ade jageg Cj ef GdJjGQjf hde jecf JUfjag Vef hGMO efgeG, acGf eQahVkG efgeG cdjgeG(B. (3dcf ZQHI eGdc Hf fHj bO BPfJ HGdCahd Ydi eG jHOh, aCacGQg GdJj GSJYUJ Ydi Gdage dOi CLjGd GdfcHI hGdEfJcGS GdMVGQj, bO CNPJ WQjbgG GdBf Edi Ljd GdTHGH GdPj GSJgOag eGdc, hNUg Hbhdg(B: "(3QHeG GdChai Cf CNU HGdUaMGJ GdbGOeI LjdkG SjCJj(B: (3jYbH Ljdj, dfDcO dge (B- (3hge Hjf CfbGV YGdefG (B- (3Cf Ydjge hGLH HfGA YGde NGU Hge(B". (3hEdi gPG GdLjd GdPj JWdY Edjg eGdc Hf fHj bHd CcKQ ef SJjf YGekG, JJbOe OGQ GdacQ HeTQhYgG (B((3GdCYeGd GdcGedI deGdc Hf fHj(B) (3LeYJgG dg aj eLehYI hGMOI, QJHJgG HMSH JGQjN JCdjagG, dJJjM dg aQUI GdEWdGY Ydi MQcI CacGQg, ef Cjf HOCJ, hcja feJ hJWhQJ, hUfYJ dgG dChd eQI agGQS eaUdI dcdeGJgG hehVhYGJgG GdeaJGMjI dcj JjSQ dg GdhUhd Edi cfhRgG, hQUO GdCTcGd hGdCSGdjH GdeJYOOI GdJj JfGhdgG ajgG, hQHW HYVgG HHYV dJTcjd UhQI TGedI dgG(B.s
(3eLehYI eGdc Hf fHj aj NeSI eLdOGJs
Keywords: (3GdcJGH hGdhSW GdEfSGfjs; (3agGQS GdBjGJ GdbQBfjI s; (3cJGH MOjK aj GdHfGA GdLOjOs; (3eLGdS OTbs